Women's rights in Central Asia: a comparative historical analysis - Safoeva Shahnoza Toyir qizi (Genius Journals, 2023)
Gender equality is not just a human right, it is a great opportunity for society to overcome some of the most pressing challenges of our time, from economic crises and global pandemics to climate change and rising poverty. Being disproportionately affected by these issues, women have the ideas and leadership to address them. This article provides a brief analysis of the modern development of women's rights in the post-Soviet space, Central Asia. In brief, such countries as Kazakhstan, Uzbekistan, Tajikistan, Turkmenistan, and Kyrgyzstan are compared with each other
Keywords: gender equality; human rights; women’s rights; Central Asia